Improving Cutting Tool Selection in Milling Processes Using Early Cost-Base Valuation - Prianggada Indra Tanaya (Universitas Katolik Parahyangan, 2022)
Selecting cutting tools for a milling process is crucial to determine the optimal cut. Minimizing milling process-cost is one of the most common optimization objectives, and thus it determines the best cutting tool to be used. However, the chosen cutting tool might not bring the optimal result based on the tool’s cost. Therefore, a valuation method based on the process and cutting-tool costs results were developed and analyzed to improve the cutting tool selection process. A specific rough-milling operation was entered to the quick cost-estimation and optimization application, and several cutting-tools were compared based on the process-cost by each tool. Using a weight-based analysis on both process-cost and tool-cost changes the cutting-tool options' initial rankings. This study showed that using different weight ratios altered the order of the most suitable cutting tools. Another finding revealed in this study is how deflection constraint affected the rank of cutting tool selection. Thus, knowing the proper limit of deflection is crucial to validate the cutting tool selection outcome.